Heat storable heat-conductive material

The heat-storing thermally conductive material, composed of a heat-storing material, thermally conductive filler, base resin, and connecting particles, addresses the challenge of filling narrow gaps by enhancing flowability and thermal conductivity, achieving effective heat storage and dissipation.

JP2025042970APending Publication Date: 2025-03-28MITSUBISHI MATERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023150209
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing flowable heat-retaining heat-conductive materials face challenges in filling narrow gaps without creating gaps, due to high viscosity and reduced hardness, which limits their thermal conductivity and heat storage effectiveness.

Method used

A heat-storing thermally conductive material comprising a heat-storing material, a thermally conductive filler, a base resin, and connecting particles, where the heat-storing material includes an alkane with 16 or more carbon atoms or a fatty acid, and the thermally conductive filler includes ceramic particles, such as aluminum oxide, to enhance flowability and thermal conductivity.

Benefits of technology

The material achieves excellent fillability in narrow spaces without gaps, while maintaining high thermal conductivity and substantial heat storage capacity, thereby extending the operational time of heat-generating components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025042970000005
    Figure 2025042970000005
  • Figure 2025042970000001
    Figure 2025042970000001
  • Figure 2025042970000002
    Figure 2025042970000002
Patent Text Reader

Abstract

To provide a heat storable heat-conductive material which has such as flowability as to be capable of being filled into a narrow part without a gap, and has high heat conductivity and a large heat storage quantity.SOLUTION: A heat storable heat-conductive material contains a heat storable material, a heat-conductive filler, a base resin, and connection particles in which primary particles are connected to each other, wherein when the total amount of the heat storable material and the base resin is 100 pts.mass, 2 pts.mass or more and 15 pts.mass or less of the connection particles are contained.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a heat storage thermally conductive material. [Background technology]

[0002] Heat transfer materials that are provided between a heat generating body and a heat dissipating member and transmit heat are known in various forms, such as grease type, gap filler type, and sheet type. By using these heat transfer materials, for example, heat generated by a heat generating body can be efficiently dissipated from a heat dissipating member such as a metal case or a heat sink. By providing such a heat transfer material between a heat generating body and a heat dissipating member, the thermal resistance between the heat generating body and the heat dissipating member can be reduced.

[0003] In the field of automotive parts, the market for lithium ion batteries (LIBs) and the like has expanded in recent years as a power source for automobiles such as electric vehicles (EVs), but the battery cases of secondary batteries such as lithium ion batteries (LIBs) have a problem in that the heat generated by the secondary batteries during charging and discharging tends to accumulate inside the case due to compactness and high output, causing the secondary batteries to reach their maximum operating temperature in a short period of time. In particular, automotive parts and the like are sometimes exposed to thermally harsh environments in which the interior temperature of the automobile can reach 40°C or higher, and under such high-temperature conditions, the secondary batteries quickly reach their maximum operating temperature, causing a problem in that the continuous operating time of the batteries is shortened.

[0004] For this reason, there is an urgent need to develop a heat dissipation design for such secondary batteries. In particular, in the case of lithium-ion secondary batteries, if a high-temperature state that exceeds the operating temperature limit continues for a long period of time, the battery may be damaged. Therefore, there is an urgent need for heat countermeasures that suppress and mitigate the temperature rise of the battery (for example, see Patent Document 1).

[0005] The use of a heat storage material is an effective heat dissipation measure for components that are used in thermally severe ambient conditions and therefore have difficulty in obtaining a temperature difference with the ambient environment. In Patent Document 1, a combination of a thermoplastic base polymer, a thermally conductive filler, and a heat storage material ensures a molded body with a predetermined hardness and improves adhesion to the heat dissipation object, and also increases the effect of suppressing and mitigating the temperature rise of a heat dissipation object that is in a condition where it is difficult to obtain a temperature difference with the ambient environment due to the influence of a thermally severe ambient environment temperature (ambient temperature).

[0006] In particular, if the heat dissipation target is a lithium-ion battery or the like, the use of a heat storage material that utilizes latent heat and has a phase change temperature within the operating temperature range of the battery can mitigate the temperature rise of the battery within the operating temperature range of the battery. In this case, if the heat storage material alone is used, the temperature will rise again once the limit of the heat storage capacity is exceeded, limiting the heat dissipation effect, but by including a thermally conductive filler, a heat conduction path is secured, improving heat dissipation properties and enabling the extension of the operable time (see, for example, Patent Document 1).

[0007] In addition, for applications in which such heat storage thermal conductive materials are injected into heat generating parts, grease-type heat storage thermal conductive materials with fluidity have been proposed. As the components of various electronic devices become finer, there is a demand for such grease-type heat storage thermal conductive materials that can be injected and filled into narrower spaces without creating voids. For example, Patent Document 2 discloses a heat storage thermal conductive material that has low hardness and high thermal conductivity, obtained by adding a heat storage substance, a thermally conductive filler, and a process oil to a thermoplastic base polymer. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 6893741 [Patent Document 2] Patent No. 7211923 Summary of the Invention [Problem to be solved by the invention]

[0009] However, the heat storage thermal conductive material having fluidity disclosed in Patent Document 2 contains a thermoplastic base polymer, so the viscosity of the heat storage material in a molten state is high, and there is a problem that it is difficult to inject it into narrow gaps between fine parts arranged at high density without generating voids. In addition, since the hardness of the composition is reduced by increasing the blending ratio of process oil that does not contribute to improving heat storage and thermal conductivity, the effect of improving heat storage and thermal conductivity is limited, and there is also a concern that the process oil will bleed out.

[0010] The present invention has been made in consideration of the above background, and aims to provide a heat storage thermal conductive material that has fluidity enabling it to fill narrow areas without gaps, and that has high thermal conductivity and a large amount of heat storage. [Means for solving the problem]

[0011] In order to solve the above problems, the heat storage thermal conductive material of one embodiment of the present invention proposes the following means. (1) The heat storage thermal conductive material of aspect 1 of the present invention comprises a heat storage material, a heat conductive filler, a base resin, and connecting particles in which primary particles are connected to each other, and is characterized in that the connecting particles are contained in an amount of 2 parts by mass or more and 15 parts by mass or less when the total amount of the heat storage material and the base resin is 100 parts by mass.

[0012] (2) A second aspect of the present invention is the heat storage thermally conductive material of the first aspect, characterized in that the heat storage material contains an alkane having 16 or more carbon atoms or a fatty acid.

[0013] (3) A third aspect of the present invention is the heat storage thermal conductive material of the first or second aspect, characterized in that the thermal conductive filler contains ceramic particles.

[0014] (4) A fourth aspect of the present invention is characterized in that, in the heat storage thermal conductive material of any one of the first to third aspects, the base resin contains polyurethane made of a polyol having two or more hydroxyl groups in one molecule and an isocyanate having two or more functional groups in one molecule that can react with the hydroxyl groups of the polyol.

[0015] (5) A fifth aspect of the present invention is the heat storage thermal conductive material according to any one of the first to fourth aspects, wherein the connected particles are formed by fusing the primary particles having an average particle diameter of 70 nm or less to form a beaded network, and the specific surface area is 35 m 2 / g or more.

[0016] (6) A sixth aspect of the present invention is the heat storage thermal conductive material according to any one of the first to fifth aspects, characterized in that the heat storage thermal conductive material further contains a dispersant.

[0017] (7) A seventh aspect of the present invention is characterized in that, in the heat storage thermal conductive material of the sixth aspect, the dispersant contains a nonionic surfactant.

[0018] (8) An eighth aspect of the present invention is the heat storage thermal conductive material according to any one of the first to seventh aspects, characterized in that the heat storage thermal conductive material has a viscosity of 500 Pa·s or less before curing. Effect of the Invention

[0019] According to the present invention, it is possible to provide a heat storage thermally conductive material that has flowability enabling it to fill narrow areas without leaving any gaps, and also has high thermal conductivity and a large amount of heat storage. [Brief description of the drawings]

[0020] [Figure 1] FIG. 2 is a schematic diagram showing a method for evaluating the filling property in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, a heat storage thermal conductive material according to an embodiment of the present invention will be described with reference to the drawings. Note that the following embodiments are specifically described to better understand the gist of the invention, and do not limit the present invention unless otherwise specified.

[0022] The heat storage thermally conductive material of the present embodiment includes a heat storage material, a thermally conductive filler, a base resin, and connecting particles in which primary particles are connected to one another. The heat storage material is intended to enhance the effect of suppressing and mitigating the temperature rise of a heat dissipation object that is in a condition where it is difficult to obtain a temperature difference with the surrounding environment due to the influence of the thermally severe surrounding environment temperature (ambient temperature). An example of such a heat storage material may be an alkane having 16 or more carbon atoms, that is, paraffin. An example of paraffin is normal paraffin (particularly a mixture of alkanes having 16 to 40 carbon atoms). In this embodiment, normal paraffin having a melting point of 43°C and a latent heat of fusion of 190 J / g is used as an example of a heat storage material. The number of carbon atoms depends on the temperature range to be stored, but is preferably 16 to 40. In this case, the melting point is about 18°C ​​to 81°C, which is suitable for the application of the present invention.

[0023] Paraffin is a solid-liquid phase transition type latent heat storage material, which changes from a solid phase to a liquid phase when absorbing heat from a heat dissipation object, and stores heat by the latent heat of the phase change (melting).

[0024] Among the solid-liquid phase transition type latent heat storage materials, paraffin in particular has a relatively large latent heat and a large amount of heat storage per unit volume, and can obtain stable heat dissipation and heat storage even if it is repeatedly melted and solidified. In addition, it does not corrode the heat dissipation object, is inexpensive, and furthermore, the phase change temperature (melting point) can be easily adjusted according to the molecular weight, etc., making it a preferable property as a heat storage material.

[0025] The latent heat storage material may contain an alkane having 16 or more carbon atoms or any fatty acid. Examples of fatty acids include dodecanoic acid, which has a melting point of 44°C, tetradecanoic acid, which has a melting point of 54°C, hexadecanoic acid, which has a melting point of 63°C, and docosanoic acid, which has a melting point of 82°C.

[0026] In this way, when using a phase change material such as a solid-liquid phase transition type as a heat storage material, a material according to the required phase change temperature (which corresponds to the melting point in the case of a solid-liquid phase change material), i.e., a material having a phase change temperature (melting point) in the desired temperature range, can be selected.

[0027] Specifically, from the viewpoint of performance and durability, it is preferable that the latent heat temperature range is in the range of 18°C ​​or more and 81°C or less. If the latent heat temperature range is less than 18°C, the heat storage capacity will quickly exceed its limit at high temperatures, and there is a concern that it will be difficult to effectively suppress the temperature rise of the battery. If the latent heat temperature range is more than 81°C, the battery will become too hot even at temperatures below the melting point of the heat storage material, and there is a possibility that the characteristics will deteriorate.

[0028] The thermally conductive filler transmits the heat of the heat dissipation object or the heat stored in the heat storage material toward the low temperature side. The thermally conductive filler may be in the form of a powder or particles that can be uniformly mixed with the base resin. In addition, when the heat storage thermally conductive material of this embodiment is applied to a heat dissipation medium such as an electric component or a semiconductor element, it is preferable to use an insulating material as the thermally conductive filler. By using an insulating thermally conductive filler, the heat storage thermally conductive material can also be made insulating.

[0029] The thermally conductive filler may be, for example, ceramic particles having insulating properties, and specifically includes metal oxides such as aluminum oxide, magnesium oxide, titanium oxide, zinc oxide, silicon oxide, beryllium oxide, copper oxide, zirconium oxide, and calcium oxide, and metal nitrides such as boron nitride, aluminum nitride, and silicon nitride. Of these, aluminum oxide and boron nitride are preferred as the thermally conductive filler. Aluminum oxide is particularly preferred as a component of the thermally conductive filler because it is inexpensive and easily available. In this embodiment, aluminum oxide (alumina) is used as the thermally conductive filler. In this embodiment, the thermally conductive filler refers to a filler having a higher thermal conductivity than the base resin.

[0030] In addition, the thermally conductive filler has a specific surface area of ​​0.5 m 2 It is preferable to use particulate matter having a molecular weight of at least 100 / g and an average particle size (d50) of 40 μm or less. The specific surface area of ​​the thermally conductive filler is 0.5 m 2 If the specific surface area is less than 400 m2 / g, there is a concern that the heat storage thermal conductive material will become fluid and flow out of the placement area in the temperature range where the heat storage material is at or above its melting point. There is also a concern that the heat conductive filler will settle and the heat storage thermal conductive material will become non-uniform. There is no particular upper limit on the specific surface area of ​​the heat conductive filler, but the specific surface area of ​​the heat conductive filler should be less than 400 m2. 2 / g or less is desirable.

[0031] On the other hand, if the average particle size (d50) of the thermally conductive filler measured by a laser diffraction scattering type particle size distribution measuring device (MT3300EXII: manufactured by Microtrack Bell Co., Ltd.) exceeds 40 μm, there is a concern that the thermal storage thermal conductive material will become fluid and flow out from the placement location in the temperature range where the thermal storage material is at or above its melting point. There is also a concern that the thermally conductive filler will precipitate and the thermal storage thermal conductive material will become non-uniform. There is no particular lower limit for the average particle size of the thermally conductive filler, but it is desirable for the average particle size of the thermally conductive filler to be 0.005 μm or more.

[0032] The thermally conductive filler is mixed in such a ratio that the thermally conductive filler is 30 parts by mass or more when the thermal storage material is 90 parts by mass. If the thermally conductive filler is less than 30 parts by mass when the thermal storage material is 90 parts by mass, the thermal storage material may become fluid in a temperature range where the thermal storage material is at or above its melting point, and the thermally conductive material may flow out from the placement location. Note that it is preferable that the thermally conductive filler is 3000 parts by mass or less when the thermal storage material is 90 parts by mass.

[0033] The base resin is a substrate in which the heat storage material and the thermally conductive filler are dispersed. Specific examples of base resins include polyurethane (PU) resin, polyamide (PA) resin, polyacetal (POM) resin, polycarbonate (PC) resin, modified polyphenylene ether resin, polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, polyethylene (PE) resin, polypropylene (PP) resin, polyvinyl chloride (PVC) resin, polystyrene (PS) resin, ABS resin, and acrylonitrile styrene (AS) resin.

[0034] In this embodiment, among these base resins, a polyurethane (PU) resin containing a polyol having two or more hydroxyl groups in one molecule and an isocyanate having two or more functional groups in one molecule that can react with the hydroxyl groups of the polyol is used as the base resin. The following formula 1 shows an example of the structural formula of the polyol component. Formula 2 shows an example of the structural formula of the isocyanate component. Formula 3 shows an example of the structural formula of the polyurethane (PU) resin.

[0035] [ka]

[0036] [ka]

[0037] [ka]

[0038] The mixing ratio of the base resin, heat storage material, and thermally conductive filler is preferably in the range of 1 to 3,000 parts by mass of the heat storage material and 30 to 3,000 parts by mass of the thermally conductive filler per 10 parts by mass of the base resin.

[0039] The connected particles are primary particles connected to each other. For example, the connected particles may be primary particles having an average particle diameter (d50) of 70 nm or less fused together to form a beaded network. The connected particles may also be branched beads forming a beaded network.

[0040] In this embodiment, fumed silica is used as the linked particles. Fumed silica is a high-purity amorphous fine powder silica produced by hydrolysis in an oxyhydrogen flame using silicon tetrachloride as a raw material. Spherical particles (diameter 5 to 70 nm) formed by combustion are fused in a beaded shape to form bulky aggregates (particle diameter about 100 to 400 nm). The particle diameter of such aggregates can be measured by, for example, TEM. Such fumed silica can be obtained by arbitrarily controlling the particle diameter and specific surface area by changing the production conditions such as the temperature of the oxyhydrogen flame during production and the supply ratio of silicon tetrachloride, oxygen, and hydrogen.

[0041] By incorporating such fumed silica as a constituent component of the heat storage thermal conductive material, it is possible to adjust the viscosity of the heat storage thermal conductive material before curing to an appropriate level that prevents the thermal conductive filler of the heat storage thermal conductive material from settling and separating.

[0042] Fumed silica can be divided into hydrophilic fumed silica and hydrophobic fumed silica depending on its properties against water. Fumed silica has hydrophilic silanol groups (Si-OH) and hydrophobic siloxanes (Si-O-Si) on the surface. The silanol groups are chemically active, and fumed silica produced by hydrolysis is hydrophilic fumed silica. By reacting this hydrophilic fumed silica with an appropriate organic treatment agent, such as silane, hydrophobic fumed silica can be produced. In this embodiment, either hydrophilic or hydrophobic fumed silica can be used, or a mixture of these can also be used.

[0043] In the heat storage thermal conductive material of this embodiment, the content (mixing ratio) of the linked particles, typified by fumed silica, is in the range of 2 parts by mass or more and 15 parts by mass or less when the total amount of the heat storage material and the base resin is 100 parts by mass. If the content of fumed silica is less than 2 parts by mass, there is a concern that the thermally conductive filler may settle and separate from the heat storage thermal conductive material, whereas if the content of fumed silica is more than 15 parts by mass, there is a concern that the fluidity is low and the heat storage thermal conductive material may not be able to fill fine gaps.

[0044] In this embodiment, the linked particles, typified by fumed silica, have a specific surface area of ​​35 m2 as measured by the BET (Brunauer-Emmett-Teller) method. 2 / g or more, 400m 2 / g or less. Preferably, it is 50m 2 / g or more, 380m 2 The BET method is a method in which molecules with a known adsorption area are adsorbed onto the powder particle surface at low temperature, and the specific surface area of ​​the sample is calculated from the amount of adsorption.

[0045] The specific surface area of ​​the connected particles is 35m 2 If the viscosity is less than 1 / g, the fluidity of the heat storage thermal conductive material will be too low, and there is a concern that the heat storage thermal conductive material will not be able to fill minute gaps.

[0046] The heat storage thermally conductive material of this embodiment preferably further contains a dispersant. The dispersant prevents the aggregation of the thermally conductive filler constituting the heat storage thermal conductive material, for example, ceramic particles, and disperses the ceramic particles appropriately in the heat storage thermal conductive material. Such a dispersant can stably disperse the ceramic particles in the heat storage thermal conductive material by the action of repulsion between particles due to electric charge and physical separation between particles due to the dispersant component adhering to the outer peripheral surface of the ceramic particles so that the dispersed ceramic particles do not re-aggregate.

[0047] Examples of such dispersants include sodium polycarboxylate, ammonium polycarboxylate, alkylamine polycarboxylate, amino alcohol polyphosphate, nonionic surfactants, etc. In this embodiment, a nonionic surfactant is used as the dispersant.

[0048] Nonionic surfactants are surfactants that have hydrophilic groups that do not ionize when dissolved in water. Examples of nonionic surfactants include ester-type surfactants, such as glycerin fatty acid esters, sorbitan fatty acid esters, and sucrose fatty acid esters, which are formed by ester bonds between polyhydric alcohols such as glycerin, sorbitol, and sucrose (cane sugar) and fatty acids. Ether-type surfactants include alkylphenol-based polyoxyethylene alkylphenyl ethers. Ester-ether-type surfactants include fatty acid-based polyoxyethylene sorbitan fatty acid esters.

[0049] The heat storage thermal conductive material having the above-mentioned structure preferably has a viscosity of 500 Pa s or less before curing. If the viscosity exceeds 500 Pa s before curing, the fluidity of the heat storage thermal conductive material becomes too low, and there is a concern that the heat storage thermal conductive material cannot be filled into minute gaps.

[0050] According to the heat storage thermal conductive material having the above-mentioned configuration, in order to prevent the melted heat storage material and the thermal conductive filler from separating and decreasing the filling property during injection, by adding connecting particles such as fumed silica and a dispersant, it is possible to realize a heat storage thermal conductive material having the contradictory properties of preventing separation between the heat storage material and the thermal conductive filler and improving fluidity. In other words, it is possible to obtain a heat storage thermal conductive material that prevents separation between the heat storage material and the thermal conductive filler, has fluidity that allows filling narrow parts without gaps, has high thermal conductivity, and stores a large amount of heat.

[0051] Although one embodiment of the present invention has been described above, this embodiment is presented as an example and is not intended to limit the scope of the invention. This embodiment can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the gist of the invention. This embodiment and its modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and gist of the invention. EXAMPLES

[0052] The effect of the heat storage thermal conductive material of the present invention was examined. (Sample Preparation) (a) The heat storage material, the thermally conductive filler, the polyol (a component of the base resin), the connecting particles, and the dispersant are each weighed out and mixed. (b) The mixture of (a) is heated to a temperature equal to or higher than the melting point of the thermal storage material to melt the thermal storage material. (c) The mixture obtained in (b) is mixed and kneaded. (d) The kneaded material obtained in (c) is placed in a dispenser and heated to a temperature equal to or higher than the melting point. (e) Isocyanate (a component of the base resin) is added to and mixed with the kneaded material obtained in (d) to obtain a pre-cured heat storage thermal conductive material. (f) The uncured heat storage thermal conductive material obtained in (e) is dispensed from a dispenser, and the viscosity and filling property are evaluated. (g) The heat storage thermal conductive material before curing after being pressed out is left to stand in the air at 70°C for 24 hours to polymerize and cure the polyol and isocyanate, forming polyurethane (PU) as the base resin, and obtaining a cured heat storage thermal conductive material. (h) The thermal conductivity and heat storage capacity of the cured heat storage thermal conductive material obtained in (g) are evaluated.

[0053] The components are as follows: Heat storage material: Docosane (C 22 H 46 ) Melting point: 44.4℃ Thermally conductive filler: Alumina (AL43A: manufactured by Sumitomo Chemical Co., Ltd.) Base resin: Urethane resin (polymerization product of polyol and isocyanate) Connected particles: fumed silica (Aerosil (registered trademark) R972: manufactured by Nippon Aerosil Co., Ltd.) Dispersant: Non-ionic surfactant (SN Dispersant 9228: manufactured by San Nopco Ltd.)

[0054] The viscosity was measured using a rheometer (model number DISCOVERY HR20: manufactured by TA Instruments Co., Ltd.) at a temperature of 50 (° C.) and a shear rate of 0.1 (1 / s). The filling property was evaluated according to the evaluation method shown in FIG. 1, in which the thickness of the spacer was varied and the minimum width into which the punched sample could fit was measured. The thermal conductivity was measured by a steady-state method using a resin material thermal resistance measuring device (PCM series: manufactured by Hitachi Technology & Services Co., Ltd.). The amount of heat storage was measured using a differential scanning calorimeter (DSC) (DSC7020: manufactured by Hitachi High-Tech Science Corporation). The compositions of the samples of Examples 1 to 12 and Comparative Examples 1 and 2, and the results of the evaluation items are shown in Table 1.

[0055] [Table 1]

[0056] According to the results shown in Table 1, the samples of Examples 1-12, which contain a heat storage material, a thermally conductive filler, a base resin, and linked particles in which primary particles are linked to each other, and contain the linked particles in a range of 2 parts by mass or more and 15 parts by mass or less when the total amount of the heat storage material and the base resin is 100 parts by mass, all had a viscosity before curing of 500 (Pa s) or less, excellent filling ability in small areas, and even after curing, a thermal conductivity of 0.9 (W / mK) or more and a heat storage capacity of 40 (J / g) or more. This confirmed that it was possible to realize a heat storage thermal conductive material that is excellent in filling ability and can achieve both high thermal conductivity and excellent heat storage ability even after curing.

[0057] On the other hand, in Comparative Example 1, which did not contain linking particles, the thermally conductive filler settled and separated from the heat storage thermally conductive material, causing it to clog the dispenser and making it impossible to dispense. Also, in Comparative Example 2, in which the proportion of linking particles exceeded 15 parts by mass, the viscosity before curing was significantly higher than 500 (Pa s), and the fluidity was low, making it impossible to fill narrow gaps.

[0058] From the above results, it has been confirmed that the heat storage thermal conductive material of this embodiment, which contains a heat storage material, a thermally conductive filler, a base resin, and linked particles in which primary particles are linked to each other, and contains the linked particles in a range of 2 parts by mass or more and 15 parts by mass or less when the total amount of the heat storage material and the base resin is 100 parts by mass, is a heat storage thermal conductive material that combines excellent filling ability into microspaces with high heat storage capacity and thermal conductivity.

Claims

1. The present invention relates to a heat storage material, a heat conductive filler, a base resin, and connecting particles in which primary particles are connected to each other, A heat storage thermal conductive material, comprising the linked particles in an amount of 2 parts by mass or more and 15 parts by mass or less when the total amount of the heat storage material and the base resin is 100 parts by mass.

2. 2. The heat storage thermal conductive material according to claim 1, wherein the heat storage material contains an alkane having 16 or more carbon atoms or a fatty acid.

3. 3. The heat storage thermal conductive material according to claim 1, wherein the thermal conductive filler contains ceramic particles.

4. The heat storage thermal conductive material according to claim 1 or 2, characterized in that the base resin contains polyurethane consisting of a polyol having two or more hydroxyl groups in one molecule and an isocyanate having two or more functional groups in one molecule that can react with the hydroxyl groups of the polyol.

5. The connected particles are formed by fusing the primary particles having an average particle diameter of 70 nm or less to form a bead-like network, and have a specific surface area of ​​35 m 2 3. The heat storage thermal conductive material according to claim 1, wherein the thermal conductive material has a molecular weight of 1 / g or more.

6. 3. The heat storage thermal conductive material according to claim 1, further comprising a dispersant.

7. The heat storage thermal conductive material according to claim 6, wherein the dispersant contains a non-ionic surfactant.

8. 3. The heat storage thermal conductive material according to claim 1, wherein the heat storage thermal conductive material has a viscosity of 500 Pa·s or less before curing.

Citation Information

Patent Citations

  • Composition for exothermic molded bodies

    JP6893741B2

  • Components for exothermic molding

    JP7211923B2